Implementasi Pengorganisasian dan Pengarahan dalam Konteks Manajemen Sekolah di SMPN 1 Kota Bandung - Melvin Christian Abimanyu; Surani Erni Morowati; Hana Alifah Putri; Najwa Ananda Mariana (Lembaga Pengembangan Kinerja Dosen, 2025)
Schools play a strategic role in developing students’ potential and preparing them to face the challenges of a dynamic life. This study aims to analyze the implementation of organizational management at SMP Negeri 1 Kota Bandung. The research employs a descriptive qualitative method with data collection techniques including observation, interviews, and document analysis. The objective is to understand the processes of planning, organizing, directing, and evaluating school management. The findings indicate that school management organization is carried out by emphasizing the role of the principal as the main leader and coordinator. This is demonstrated through efforts to effectively allocate resources, conduct teacher training, develop student socialization activities, and establish constructive relationships between the school and parents. The results show that good management positively impacts creating a conducive learning environment and achieving educational goals. This study provides theoretical and practical contributions to understanding the importance of systematic and sustainable school management.